Identifying the features of mechanical and physicochemical characteristics of polyethersulfone membranes using electric field method for water filtration applications - Firdaus, Aneka; Dani, Rahma; Gantada, Muhammad Satya Putra; Ismail, Ahmad Fauzi; Nukman, Nukman; Bizzy, Irwin; Mataram, Agung (Eastern-European Journal of Enterprise Technologies, 2025)
Electric-field assistant prepared polyethersulfone (PES) membranes were selected as the research object in this paper, aiming to address how to control membrane morphology, mechanical property and water permeation at the same time through a simple and environmentally friendly method for filtration purposes. Three PES membranes were fabricated and denoted as MP1 (25% PES), MP2 (30% PES) and MP3 (35% PES). Results indicated that the electric field can be used as a feasible method to design desired membrane structure and performance, SEM observations shows average pore sizes of 0.062–0.095 μm, AFM images showed MP1 has rough surface with larger pores, and MP3 has smoother surface with finer pores. Tensile test results as well indicated that the mechanical properties of MP were evidently reinforced when adding PES, and all tensile strengths increased monotonous with increase in the concentration of PES, wherein MP3 had the best maximum tensile strength (5.64907407 MPa). FTIR spectra were in agreement with characteristic PES functional groups, XRD showed an overall amorphous nature and some semi-crystalline order developed that was predominantly exerted along the vertical direction to the support surface with concentration within PES-rich membranes. These findings account for the reported compromise of the filtration performance, MP1 presented in NWP with best permeability (4.2012164.L.m⁻2·h⁻1). bar⁻1; MP3 had better mechanical stability to the detriment of flux. All tests results demonstrated how membranes can be tailored to maximize either permeability (MP1) or mechanical strength and selectivity (MP3), thereby allowing them to be employed as direct water filtration materials and could be utilized as a support for advanced composite membrane systems.